First record of the swimming sea cucumber Enypniastes eximia Théel, 1882 (Echinodermata: Holothuroidea) in Peruvian waters - Solís-Marín, Francisco Alonso (2012)
Enypniastes eximia Théel, 1882 (Echinodermata: Holothuroidea) a swimming sea cucumber is reported for the first time from Peru. The species was collected in the Continental rise (563-1,201 m) off Trujillo Department. Reference material has been deposited in the Coleccion Cientifica del Instituto del Mar del Peru (IMARPE), Lima, Peru.